DISTORTION OF COLOR IMAGES ON FLAT COMPUTER SCREEN DUE TO CHROMOSTEREOPSIS - Maris Ozolinsh; Kristine Muizniece; Gunta Krumina (European Scientific Journal, ESJ, 2014)
Illusory depth sense observing colour planar image such as images presented on computer screen is studied. The effect is binocular and is based on human stereovision, i.e., stereopsis. The colour difference threshold needed to induce the depth sense is determined. The effect polarity reversal – the source image red plane in front of blue plane is observed by partial covering of eye pupils medially or laterally. It is explain by the changes of eye point spread function taking into account coloured ray source and longitudinal chromatic eye aberrations. Image lightness affects the inducing of colour stereopsis due to changes of eye pupil size. Illusory depth sense is essential when designing colour graphical output on computer screen.